Ambient ultraviolet radiation: A new factor affecting anaerobic fermentation of oat and subsequent methane emissions. (July 2022) - Xie, Yixiao; Sun, Hong; Zhang, Changbing; Cheng, Qiming; Zheng, Yulong; Wang, Chunmei; Xiao, Bingxue; Li, Ping; Chen, Chao
Graphical abstract: Highlights: Molasses and Lactobacillus plantarum promoted anaerobic fermentation of oats. Attenuated UV radiation had an enriching effect on epiphytic bacteria of forage. The fermentation quality of silage was indirectly enhanced by attenuated UV radiation. Strong UV radiation may indirectly reduce greenhouse gas emissions after silage feeding. Low UV radiation from energy crops may indirectly enhance silage biogas production. Abstract: To investigate the effect of ambient ultraviolet (UV) radiation on the Qinghai-Tibetan Plateau on anaerobic fermentation and subsequent methane emissions, oats grown under different ambient UV conditions (UV1, 100% ambient UV radiation; UV2, 50% ambient UV radiation) were fermented with molasses and Lactobacillus plantarum (LP) inoculant treatments. The UV2 treatment increased ( P < 0.05) epiphytic bacterial counts and reduced ( P < 0.05) the water-soluble carbohydrate contents of oat. Both the UV2 treatment and the LP inoculant substantially increased the abundance of Lactobacillus and inhibited detrimental microorganisms (enterobacteria and yeasts) during anaerobic fermentation, resulting in the absence of butyric acid. The UV2 treatment increased ( P < 0.05) the acid detergent fiber contents after anaerobic fermentation and indirectly increased ( P < 0.05) methane emissions by 8.52–14.69% during in vitro ruminal digestion. This study demonstrated that low ambient UV radiation during cultivation facilitated anaerobic fermentation and consequently enhanced subsequent methane emissions from the rumen.